'It promoted a positive culture around falls prevention': staff response to a patient education programme—a qualitative evaluation. Issue 12 (21st December 2016) - Hill, Anne-Marie; Waldron, Nicholas; Francis-Coad, Jacqueline; Haines, Terry; Etherton-Beer, Christopher; Flicker, Leon; Ingram, Katharine; McPhail, Steven M
Abstract : Objectives: The purpose of this study was to understand how staff responded to individualised patient falls prevention education delivered as part of a cluster randomised trial, including how they perceived the education contributed to falls prevention on their wards. Design: A qualitative explanatory study. Methods: 5 focus groups were conducted at participatory hospital sites. The purposive sample of clinical staff (including nurses, physiotherapists and quality improvement staff) worked on aged care rehabilitation wards when a cluster randomised trial evaluating a patient education programme was conducted. During the intervention period, an educator, who was a trained health professional and not a member of staff, provided individualised falls prevention education to patients with good levels of cognition (Mini-Mental State Examination >23/30). Clinical staff were provided with training to support the programme and their feedback was sought after the trial concluded, to understand how they perceived the programme impacted on falls prevention. Data were thematically analysed using NVivo qualitative data analysis software. Results: 5 focus groups were conducted at different hospitals (n=30 participants). Staff perceived that the education created a positive culture around falls prevention and further, facilitated teamwork, whereby patients and staff worked together to address falls prevention. The educator was perceived to be a valuable member of the team. Staff reported that they developed increased knowledge and awareness about creating a safe ward environment. Patients being proactive and empowered to engage in falls prevention strategies, such as ringing the bell for assistance, was viewed as supporting staff falls prevention efforts and motivating staff to change practice. Conclusions: Staff responded positively to patient falls prevention education being delivered on their wards. Providing individualised patient education to older patients with good levels of cognition can empower staff and patients to work as a team to address falls prevention on hospital rehabilitation wards.